PERSEPSI AKUNTAN PEMERINTAH, MAHASISWA AKUNTANSI, DAN AKUNTAN PERUSAHAAN TERHADAP ETIKA BISNIS DAN ETIKA PROFESI (STUDI EMPIRIS DI DAERAH ISTIMEWA YOGYAKARTA) - Asri, Triasti Intan; Manuhara, Wahyu (Journal of Accounting and Investment, 2009)
This research focuses on the business ethics and profession ethics used for empirical study in D.I Yogyakarta. The purpose of this research was to examine the differences of perception on business ethics and profession ethics between the government accountant, the accounting student, and the company management accountant in DI Yogyakarta. The population of this research is all of the government accountants, accounting students, and company management accountants in DI Yogyakarta. The samples were 213 respondents, it consisted of 38 government accountants, 114 accounting students, and 32 company management accountants. The data were collected using questionnaires and distributions that were done with purposive sampling method. Independent sample t-test and mean were used to test of the hypothesis. The result of the hypothesis shows that there are different between perceptions government accountants and accounting students on the business ethics and profession ethics. The other results of hypothesis show that there are different perceptions between government accountants and company management accountants on the business ethics and profession ethics. On the other hand, the result of hypothesis shows that there are no different perceptions between accounting students and company management accountants on the business ethicsand profession ethics.